What supports and services post COVID-19 do children with disabilities and their parents need and want, now and into the future? - Pozniak, K.; Swain, A.; Currie, G.; Doherty-Kirby, A.; Grahovac, D.; Lebsack, J.; Campbell, W.; Humphreys, C.; Patterson, S.; Raha, S.; Whitley, J.; Kraus de Camargo, O. (Frontiers in Public Health, 2024)
Children and youth with disabilities and special healthcare needs, and their families, have been uniquely affected by the COVID-19 pandemic. However, the voices of children themselves are still not well represented in the existing literature. This qualitative descriptive study used a combination of visual methods and interviews to learn about the experiences of Canadian 2 children with disabilities (n=18) and their parents (n=14) during the COVID pandemic and into the post-pandemic period. Data collection was carried out between January and July 2023. The aim was to identify the supports and services children and families need at present and moving forward. Families' pandemic experiences were complex and nuanced. For many, the pandemic complicated and disrupted everyday activities and supports. These disruptions were largely buffered by parents. However, some families also identified unexpected benefits. Key themes pertaining to present and future needs included the need for services that are flexible; consistent; conducive to relationship-building; comprehensive; coordinated across sectors; and designed to support the needs of the whole family.